Alternative Expressions of Citizen Voices: The Protest Song and Popular Engagements with the Mozambican State - Manhiça, Anésio; Shankland, Alex; Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Tadros, Mariz (Institute of Development Studies, 2020)
This study examines Mozambican popular music to investigate three questions: Are notions of empowerment and accountability present in popular music in Mozambique? If so, what can these existing notions of empowerment and accountability reveal about relations between citizens and state institutions in general and about citizen-led social and political action in particular? In what ways is popular music used to support citizen mobilisation in Mozambique? The discussion is based on an analysis of 46 protest songs, interviews with musicians, music producers and event promoters as well as field interviews and observations among audiences at selected popular music concerts and public workshops in Maputo city. Secondary data were drawn from radio broadcasts, digital media, and social networks. The songs analysed were widely played in the past two decades (1998–2018), a period in which three different presidents led the country. Our focus is on the protest song, conceived as those musical products that are concerned with public affairs, particularly public policy and how it affects citizens’ social, political and economic life, and the relationship between citizens and the state.
Accepted: 2020-11-02T15:22:47Z ISSN: 2040-0209
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento

As regras do jogo: Uma introdução à ação normativa da Organização Internacional do Trabalho - International Labour Organization (International Labour Organization, 2019)
"As regras do jogo: uma introdução às normas internacionais do trabalho" apresenta de maneira sucinta a política normativa da OIT, com objetivo de facilitar a sua compreensão e apropriação pelos constituintes tradicionais da OIT e os do sistema das Nações Unidas, bem como os não especialistas e o público em geral.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - portuguese / português; employment / emprego

Theories of Change for Promoting Empowerment and Accountability in Fragile and Conflict-Affected Settings - Green, Duncan (IDS, 2017)
This paper explores the current state of thinking among a range of aid actors (multilaterals, bilateral, applied scholars and international non-governmental organisations) on how to promote empowerment and accountability in fragile, conflict and violence affected settings. It seeks to identify trends, gaps and weaknesses in that thinking, and propose research questions and hypotheses to test. Three underlying sources of confusion are identified that are hindering progress on both understanding empowerment and accountability in fragile, conflict and violence affected settings, and taking helpful action to promote it. They are: (1) theory of endogenous change (e.g. on how empowerment and accountability arise in situ) versus the theory of action of an external intervention; (2) fragility versus conflict: there is no clear justification for combining these different aspects into a single category; and (3) empowerment versus accountability: donor analysis and practice has been overwhelmingly weighted towards accountability, exhibiting limited understanding or interest in the nature of power.
Accepted: 2017-11-21T13:51:12Z ISSN: 2040-0209
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; conflict / conflito; empowerment / empoderamento; fragility / fragilidade

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género